Response in a hot environment: the physiological adaptation of the sub-elite para-swimming athletes - Ashadi, K.; Kuncoro, I.; Soselisa, R. A.; Budiyono, R.; Andriana, L. M.; Hasyim, Z. (Advances in Health Sciences Research, 2022)
Thermoregulation is an effort to maintain body temperature within the normal range, it`s achieved by maintaining a balance between the heat generated in the body and the heat released. The purpose of this study was to analyze the physiological adaptation response in a hot environment in the sub-elite athlete's paraswimming. The method used is quantitative with pre-test and post-test design, which examines five paraswimming athletes. The data were collected for nine weeks and includes body weight changes, temperature, and relative humidity during exercise. The analysis data used are mean, standard deviation, Wilcoxon test, and Mann-Whitney test. The results of this study are that there is a difference between the training sessions in the morning and the afternoon on the loss of body fluids of para-swimming athletes (p<0,00). The amount of fluid loss in athletes decreased every week (p<0,00). The temperature and relative humidity in the morning session was higher than in the training session in the afternoon. The decrease in the amount of bodies fluid loss is caused by various factors, including the drinking pattern strategy applied by each athlete and the athlete's body starting to adapt to the conditions of the training environment.